Septic Encephalopathy Characterized by Acute Encephalopathy with Biphasic Seizures and Late Reduced Diffusion and Early Nonconvulsive Status Epilepticus. (9th March 2016) - Yamaguchi, Hiroshi; Tanaka, Tsukasa; Maruyama, Azusa; Nagase, Hiroaki
Abstract : Infection, whether viral or bacterial, can result in various forms of brain dysfunction (encephalopathy). Septic encephalopathy (SE) is caused by an excessive immune reaction to infection, with clinical features including disturbed consciousness and seizures. Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is usually accompanied by viral infection in children and is characterized by biphasic seizures and impaired consciousness. The initial neurologic symptom of AESD is typically a febrile seizure that frequently lasts longer than 30 minutes. However, the possible forms this seizure takes are unclear. For example, it is unknown if nonconvulsive status epilepticus (NCSE) could be an early seizure symptomatic of AESD. In addition, thus far no cases of combined SE and AESD have been reported. Here, we describe the first reported case of SE with AESD that notably demonstrated NCSE as an early seizure.